2019
DOI: 10.1186/s12891-019-2534-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fracture in elderly female patients after posterior fusion with pedicle screw fixation for degenerative lumbar pathology: a retrospective cohort study

Abstract: Background There have been only a few reports of subsequent postoperative vertebral fracture following posterior spinal instrumentation fusion, especially in elderly female patients. This study attempted to evaluate the long-term prevalence of subsequent postoperative vertebral fracture in female patients aged 70 years and older who underwent spine decompression and fusion surgery with pedicle screw fixation. Methods We retrospectively reviewed prospectively collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The fracture of the endplate is one of the common complications after lumbar fusion surgery, reported with a rate of 2.2%–14.6% ( Inoue et al, 2021 ), and osteoporotic spines and older females are recognized as being at heightened risk ( Nakahashi et al, 2019 ). This study found that stress on the endplate was significantly reduced and the stress was more evenly distributed under the action of the screw than in the intact model.…”
Section: Discussionmentioning
confidence: 99%
“…The fracture of the endplate is one of the common complications after lumbar fusion surgery, reported with a rate of 2.2%–14.6% ( Inoue et al, 2021 ), and osteoporotic spines and older females are recognized as being at heightened risk ( Nakahashi et al, 2019 ). This study found that stress on the endplate was significantly reduced and the stress was more evenly distributed under the action of the screw than in the intact model.…”
Section: Discussionmentioning
confidence: 99%
“…Our data in both groups showed similar results: average age was over 70 years old, BMD T-score was < − 3.0, and BMI was over 25. In addition, osteoporosis caused by aging, or various comorbidities are apt to occur along with subsequent junctional vertebral fracture after long spinal instrumented fusion [ 18 ]. In the current study, CCI in the UIV group was higher than that in the UIV + 1 group (1.65 vs. 1.27), which implies that patients with more comorbidities might be more likely to develop instrumented fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of lumbar instrumented intervertebral fusion on the development of adjacent VCFs has been discussed in some studies, with evidence of an increased risk after spinal arthrodesis. 4,5,[19][20][21][22] Yang et al reported new VCFs in 150 of 1348 patients (11.1%) after posterior lumbar interbody fusion, with 108 of these (72%) being at adjacent segments. 19 Although no study has examined the relationship between new VCFs at the adjacent segment and bone loss after spinal instrumentation surgery directly, it is known that women, the elderly, and patients with osteoporosis have a specific higher incidence of new VCFs after spinal fusion, especially within the first 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%